1970
DOI: 10.1111/j.2042-7158.1970.tb08589.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of non-ionic surfactants at the griseofulvin-solution interface

Abstract: The adsorption from solution onto griseofulvin powder of a series of non‐ionic detergents of the polyoxyethylene glycol mono alkyl ether type is described. Results are also given for polyethylene glycol 400 and a new detergent, pentaerythritol mono‐n‐octyl ether, whose synthesis and purification is reported. The effect of temperature on the adsorption is studied and possible explanations of the variation of adsorption with temperature are based on the orientation of the molecules at the interface; this is dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Therefore, it is likely that from the increase in molecular adsorption area and in adsorbed layer thickness that the Texofor molecules were adsorbed on the surface in a loop form with both the polyoxyethylene and hydrocarbon chains attached to the surface. The results found here confirm the observations of Elworthy and Guthrie [7] who studied these surface ative agents on griseofulvin and of Kayes [6] with polystyrene latex.…”
Section: (I) Adsorption Studiessupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, it is likely that from the increase in molecular adsorption area and in adsorbed layer thickness that the Texofor molecules were adsorbed on the surface in a loop form with both the polyoxyethylene and hydrocarbon chains attached to the surface. The results found here confirm the observations of Elworthy and Guthrie [7] who studied these surface ative agents on griseofulvin and of Kayes [6] with polystyrene latex.…”
Section: (I) Adsorption Studiessupporting
confidence: 94%
“…Langmuir type isotherms were obtained over the concentration range studied. Plateau values, and published values for the adsorption of these surface active agents on griseofulvin [7], are given in table 1. The adsorbed layer thicknesses calculated from the electrophoretic data, in the absence and presence of aluminium chloride ( fig.…”
Section: (I) Adsorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…that there is adsorption of the alkyl chain onto a hydrophobic portion of the surface, by the hydrophobic effect, and also association of the ethylene oxide groups with some polar group at the surface probably by hydrogen bonding. Elworthy & Guthrie (1970) have shown that such adsorption does occur with these non-ionics on griseofulvin.…”
Section: Efect Of Surface-active Agents On Mobility and Zeta Potentialmentioning
confidence: 95%
“…Research on the properties of lecithin, non-ionic surfactants and the shape of small molecules in solution was complemented at various periods by investigation of the properties of ghatti-gum (Elworthy & George 1963,1964 the obstruction effect (Elworthy et a1 1972) and the internal viscosity (Elworthy 1971) of polymer solutions, studies on dissolution and solubilization (Elworthy & Lipscomb 1968aCorby & Elworthy 1971a, b) and crystallization (Elworthy & Worthington 1968. With Ray Rowe and David Gan-derton the pore structure of plastic matrix tablets was investigated (Rowe et a1 1972(Rowe et a1 , 1973a and a variety of physicochemical features of tablet formulations were pursued in collaboration with industry (Cole et al 1974(Cole et al , 1977Pickard et a1 1975;Chalmers & Elworthy 1976a, b, c).…”
Section: Solubilizationmentioning
confidence: 99%